Students’ perceptions of peer feedback - Levi Altstaedter, Laura; Doolittle, Peter (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
Researchers have posited that students have different perceptions of peer feedback depending on their cultural background. However, studies on American students’ perceptions of peer feedback in foreign language writing research are scarce. The purpose of this study was to investigate American students’ perceptions of peer feedback in college foreign language courses. Quantitative results showed that students had overall high perceptions of the experience, with significantly higher perceptions of receiving written comments than either reading their partner’s composition or receiving face-to-face feedback from their partner. In addition, qualitative results revealed that students reported receiving from their partners more global aspect comments, focused on organization and idea development, than local aspect comments, focused on grammar and mechanics.